Tannins of Deciduous Trees Bark As a Potential Source for Obtaining Ecologically Safe Wood Adhesives (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The bark of deciduous trees grown in Latvia: grey alder, black alder, ash tree and goat willow were sequentially extracted using solvents of increasing polarity. The data about total content of both lipophilic and hydrophilic compounds were obtained using sequentially extraction with hexane and ethanol. The highest yields of hydrophilic extractives were found for grey alder and ash tree barks (25.7% and 25.8%, respectively). Hydrophilic extract from the both alder species contained high amount (up to 12% on bark dry mass) of condensed tannins (CT) or oligomeric proanthocyanidins, whereas CT content of extract from ach tree was negligible. The main component of ethanol-water extract from alder bark was identified using 13C NMR and MALDI–TOF MS spectroscopy as a mixture of A- and B-type oligomeric procyanidins with the epicatechin units polymerization degree of 2-7. Ecologically friendly wood adhesives were obtained on the condensed tannin basis.